Differences in time-frequency representation of lower limbs myoelectric activity during single and double leg landing in male athletes - Leporace, G.; Ribeiro Pereira, G.; Nadal, J.; Batista, L. A. (Journal of Electromyography and Kinesiology, 2011)
This study compared the instantaneous median frequency (IMF) obtained by means of a Choi-Williams transform of an electromyogram of the lower-limb muscles during single-leg (SL) and double-leg (DL) landings performed by fifteen male athletes. The IMF values of the rectus femoris (RF), biceps femoris (BF) and hip adductors (HA) were compared between two landing tasks, within each landing, and before and after ground contact (GC). The IMF values of the RF did not change between landings in contrast to those of the BF, which presented from 20- to 40-ms higher SL values before GC and from 40 to 60 ms after GC. HA presented higher SL values during the 40-60 ms range before GC. Within each landing, the RF IMF decreased from 40 ms to 60 ms after GC in the SL. Similar results were found for the HA IMF, which decreased from 40 ms to 80 ms after GC. The BF IMF showed no significant change. These results suggest muscle recruitment related to anterior cruciate ligament protection since the IMF values of the RF decreased in the SL, whereas the BF IMF increased. Results for the HA showed the importance of hip muscles in stabilizing the core region, allowing the activation of distal muscles with greater safety.